Politik Anggaran Pemerintah Daerah Perspektif Maqasid Syari'ah: Studi Analisis Sektoral Pada APBD Kabupaten Bangkalan Tahun 2013-2015 - Sayyidatul Fitriyah; Moh. Qudsi Fauzy (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This research is conducted with a purpose to analyze the political budgets of Bangkalan regency in fiscal year 2013 to 2015 using maqāsid syari’ah perspective that is the adequate society of basic needs related with the protection of religions, lifes, intelligence, descendants, and wealth. The method used in this research is descriptive qualitative methods by the analyzed domain to observe the priority of government’s budgeting. The data is collected by interviews after obtaining all the realization data of budgeting in maqāsid syari’ah.The result of this research is shown that Bangkalan’s political budgeting of fiscal in 2013 to 2015 it had not depicted yet in the proper level of maqāsid syari’ah.